2000
DOI: 10.1530/eje.0.1420243
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficiency of serum IGF-I, IGF-binding protein-3 (IGFBP-3), IGF-I/IGFBP-3 molar ratio and urinary GH measurements in the diagnosis of adult GH deficiency: importance of an appropriate reference population

Abstract: Objective: To analyse the diagnostic role of serum IGF-I, IGF-binding protein-3 (IGFBP-3), IGF-I/IGFBP-3 molar ratio and urinary GH (uGH) excretion in adult GH deficiency (GHD). Design: Twenty-seven adults (age range: 18-71 years) with severe GHD, defined by a peak GH response to an insulin tolerance test below 3 mg/l in patients with at least one additional pituitary hypofunction. Reference values were established from a selected age-and body mass index-matched population (154 healthy adults grouped in four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 47 publications
3
39
1
Order By: Relevance
“…These findings have been confirmed by others who also proposed an IGF1 cut-off limit of around K2 S.D. All agree that the diagnostic reliability of low IGF1 levels is satisfactory when patients with CO severe GHD or multiple pituitary deficits are considered, particularly below 40 years of age (2,4,(11)(12)(13)(14)(15). These patients therefore do not require a GH stimulation test to make the diagnosis of adult GHD; however, it remains that patients suspected for GHD showing normal IGF1 levels must undergo provocative tests (2,4).…”
Section: How To Testsupporting
confidence: 66%
“…These findings have been confirmed by others who also proposed an IGF1 cut-off limit of around K2 S.D. All agree that the diagnostic reliability of low IGF1 levels is satisfactory when patients with CO severe GHD or multiple pituitary deficits are considered, particularly below 40 years of age (2,4,(11)(12)(13)(14)(15). These patients therefore do not require a GH stimulation test to make the diagnosis of adult GHD; however, it remains that patients suspected for GHD showing normal IGF1 levels must undergo provocative tests (2,4).…”
Section: How To Testsupporting
confidence: 66%
“…The relationship between body weight and IGF-I has been discussed previously [26]. However, no simple or age-adjusted correlation was found between IGF-I and weight among the present participants.…”
Section: Discussioncontrasting
confidence: 47%
“…The patients with pituitary deficiency had lower standard deviation (SD) scores for IGF-I and the more deficiencies they had, the lower the SD score [26]. This study, in a Spanish reference population, also compared IGFBP-3 and urinary GH samples, and concluded that a combination of two methods increased the specificity to 100% in diagnosing GHD [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the reliability of serum IGF-1 as an indicator of GH deficiency is being debated (Aimaretti et al, 1998(Aimaretti et al, , 2003Granada et al, 2000). Specifically, the consensus guidelines for the diagnosis and treatment of adults with GH deficiency conclude that, ''a normal IGF-1 does not rule out GH deficiency'' (Ho, 2007).…”
Section: Kasturi and Steinmentioning
confidence: 99%